Effect of Different Dosages and Frequency of Zinc Application on Yields, Zinc Concentration, and Uptake of Rice-Wheat Rotation and Changes in Soil Chemical Fractions of Zinc. Issue 19 (28th October 2022) - Srivastava, P. C.; Pachauri, S. P.; Pathak, Anand; Shukla, A. K.
ABSTRACT: Under intensive rice-wheat cropping system (RWCS), the information on the optimum Zn dose and frequency of application is needed for sustainable productivity of the system and maintenance of soil fertility. In a 6-year field study carried out on a sandy loam (Typic hapludoll), the effect of different dosages (0, 2.5, 5.0, 7.5, and 10.0 kg Zn ha −1 ) and frequency of Zn applications (once, alternate year, and every year) were investigated on yield and Zn nutrition of rice-wheat crops and changes in chemical fractions of Zn in soil. Based on the average grain yields of rice and wheat, it was concluded that application of 7.5 kg Zn ha −1 as zinc sulfate heptahydrate to rice in alternate years was the best practice in a typic hapludoll as it resulted in an average production of 5.67 t of rice grain and 4.53 t of wheat grain ha −1 . The practice resulted in a benefit:cost ratio of 14.2: 1 and also helped to maintain the optimum level of Zn in soil. Application of Zn markedly increased the residual Zn fraction in soils. The use of medium (5 kg Zn/ha) and high doses (7.5 and 10.0 kg Zn ha −1 ) in all years brought a significant increase in water soluble + exchangeable, organically bound, and sesquioxide bound fractions of Zn. Soil application of 7.5 kg Zn ha −1 to alternate year rice crop can be recommended under RWCS on typic hapludoll for higher grain yields, profitability, and maintenance of Zn availability.